Influence of In-situ Soil Moisture Conservation Practices with Pusa Hydrogel on Physiological Parameters of Rainfed Cotton - Ashraf, A. Mohammed; T, Ragavan; S, Naziya Begam (International Journal of Bio-resource and Stress Management, 2020)
The present study was undertaken to evaluate the impact of in-situ moisture conservation and stress management practices on crop growth indices and productivity of cotton under rainfed vertisol. The experiments were laid out at Regional Research Station, Aruppukottai, Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu during rabi season (October-December) of 2016 and 2017 in split-plot design replicated thrice using cotton variety SVPR-2. The main plot treatments consisted of different in-situ moisture conservation measures viz., Broad Bed and Furrows (I1), Ridges and Furrows (I2) and Compartmental Bunding (I3). The subplot comprises with stress management practices viz., Soil application of pusa hydrogel @ 5 kg ha-1 (S1) with different foliar spray of 1% KCl (S2), 5% Kaolin (S3), PPFM @ 500 ml ha-1 (S4), Salicylic acid 100 ppm (S5) and Control (S6). The results revealed that treatment combination of broad bed and furrow and soil application of Pusa hydrogel @ 5 kg ha-1+foliar spray of PPFM @ 500 ml ha-1 had recorded significantly higher crop growth indices like CGR, RGR, NAR, reduced proline content, higher values of relative leaf water content, chlorophyll SPAD values, yield attributes viz., sympodial branches plant-1, number of bolls plant-1, boll weight and seed cotton yield (1,786 kg ha-1).